Situs Benteng Putri Hijau: Sejarah, Mitos, dan Perspektif Masyarakat - Dwisuda, Nabila; Rohani, Laila; Susanti, Neila (Warisan: Journal of History and Cultural Heritage, 2022)
This study aims to look at the history, myths, and community perspectives regarding the Fort Putri Hijau site located in Deli Tua, Deli Serdang Regency. Putri Hijau Fort is a natural defense fort that is thought to be a relic of the Aru Kingdom. However, the existence of this site is often associated with history and myths that are still believed by the local community. This research is included in the type of field research using historical research methods. The results of this study indicate that the existence of the Putri Hijau Fort site as a cultural heritage is not widely known by the general public, let alone the surrounding community. People are much more aware that the site is just a place for bathing tours without any historical, mythical, and cultural heritage values in it. In addition, not many people know that the site is a former relic of the Aru Kingdom. Even some people from the age range of around 20-50 years who live around the location of this site, do not know about the existence of the Aru Kingdom. Some of them only know a few myths about the beauty of Putri Hijau and the greatness of Putri Hijau's brother named Mambang Yazid which has been told from generation to generation.